Narrowband feedback for narrowband control of resonant and non-resonant vibration - Kim, Sang-Myeong [UNESP]; Brennan, Michael J. [UNESP]; Abreu, Gustavo L.C.M. [UNESP] (Elsevier, 2016)
This paper presents a simple feedback methodology that uses second order filters to control narrowband resonant and non-resonant vibration of a structural system. In particular, a single degree-of-freedom system is studied throughout the paper. The idea of the methodology is based on the fact that direct feedback is effective for in-phase vibration control. Thus, the position, velocity and acceleration are respectively fed back to control the low, resonant and high frequency vibration of the system. Each of these is passed through a band pass filter of second order that is inserted to extract and feed back the in-phase signal component only. This is called narrowband feedback. It is demonstrated with experiments that narrowband feedback is useful for narrowband control of resonant and non-resonant vibration.
Keywords: Loudspeakers; Narrowband control; Narrowband feedback; Second order filters; Vibration control